Vessel speed optimisation in container shipping: A new look. Issue 4 (3rd April 2019) - Ng, ManWo
Abstract: Vessel speed optimisation has, in recent years, been recognised as a practical and important cost reduction strategy in the maritime shipping industry. This paper takes a new look at the trade-off between sailing speed and the number of vessels required to maintain a given service frequency. Fundamental insights will be revealed, shedding light on how much (or limited) choice there really is when deciding on the number of vessels to deploy. To demonstrate the significance of our revelations in an optimisation setting, a new vessel speed optimisation model is proposed. A case study shows that by incorporating our findings, computation times can be reduced dramatically, up to over 4400 times faster. This computational benefit is especially timely in the current era of alliances and consolidation in the container shipping industry, when instances of the vessel speed optimisation problem can only be expected to grow in size.